2016
DOI: 10.22440/econworld.wp.2016.003
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus of Economic Growth, Military Expenditures, and Income Inequality

Abstract: This paper examines the effect of military expenditures on economic growth by utilizing dynamic panel data analysis for 82 countries for the period of . Considering the possible effect of inequality on the military expenditures-economic growth nexus, this paper incorporates inequality along with its interaction with human capital into an augmented Solow growth model. The general finding is that military expenditures have a negative impact on economic growth, valid for several model specifications and sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
1
0
2
Order By: Relevance
“…With the help of panel regression methodology, it is determined that military expenditure has a negative effect on economic growth. Also, Dunne and Tian (2015), Pan et al (2015), Töngür and Elveren (2017), Yildirim and Öcal (2016) and Cappella Zielinski et al (2017) underlined the importance of the same issue in their studies. On the other side, there are also some studies which identified that government expenditure has a positive effect on economic growth (Adegoriola and Siyan, 2015;Aydın et al, 2016;Bunte et al, 2018;Rivero, 2017;Odhiambo, 2015).…”
Section: Literature Review On Economic Growthmentioning
confidence: 94%
“…With the help of panel regression methodology, it is determined that military expenditure has a negative effect on economic growth. Also, Dunne and Tian (2015), Pan et al (2015), Töngür and Elveren (2017), Yildirim and Öcal (2016) and Cappella Zielinski et al (2017) underlined the importance of the same issue in their studies. On the other side, there are also some studies which identified that government expenditure has a positive effect on economic growth (Adegoriola and Siyan, 2015;Aydın et al, 2016;Bunte et al, 2018;Rivero, 2017;Odhiambo, 2015).…”
Section: Literature Review On Economic Growthmentioning
confidence: 94%
“…Temuan ini berbeda dengan penelitian yang dilakukan Kalim & Hassan (2013) yang menemukan adanya kontribusi langsung dan signifikan pengeluaran militer terhadap kemiskinan di Pakistan. Selain itu, penelitian Töngür & Elveren (2015) mengungkapkan hubungan positif antara ketimpangan pendapatan dan persentase pengeluaran militer, yang menunjukkan bahwa belanja militer dapat menjadi faktor yang signifikan secara statistik yang mempengaruhi tingkat pengeluaran militer dan ketimpangan. Selain itu, penelitian Tongur juga menyoroti hubungan yang signifikan secara statistik antara kesejahteraan sosial demokrat dan rezim politik serta pengeluaran militer.…”
Section: Hasil Dan Pembahasanunclassified
“…Ayrıca, yüksek düzeydeki savunma harcamaları savunma sanayinde, diğer sektörlere yayılma potansiyeline sahip yeni bilgi ve teknolojilerin geliştirilmesini sağlamıştır. Daha sonra yapılan Ball (1983), Lipow and Antinori (1995), Akal et al, (2011), Dunne and Nikolaidou (2012), Ali and Ather (2015), Elveren (2016), Larrosa (2016), Töngür and Elveren (2017) gibi uygulamalı çalışmalarda savunma harcamalarının büyüme üzerindeki olumsuz etkilerine yönelik bulgular elde edilmiştir. Bu çalışmalar, askeri harcamalardaki artışın toplumsal ihtiyaçlar, eğitim, altyapı, sağlık gibi alanlara yönelik kaynakları azalttığını ve diğer sektörlerdeki özel yatırımları baskıladığını öne sürmektedir.…”
Section: Li̇teratür İncelemesi̇unclassified